2016
DOI: 10.4103/0019-5278.197533
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos-induced lung disease in small-scale clutch manufacturing workers

Abstract: Background:The crocidolite variety of asbestos is banned. However, chrysotile, which is not prohibited, is still used in developing countries in making products such as clutch plate. Fourteen workers from a small-scale clutch plate-manufacturing factory were analyzed for asbestos-induced lung disease as one of their colleagues had expired due to asbestosis.Aims:This study was conducted to evaluate the awareness of workers, the prevalence and type of asbestos-induced lung disease, and the sensitivity and specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…We found asbestos to be associated with COPD both in single and multi-exposure models. Our observations largely resonate with previous findings where progressive lung function decline and COPD have been reported in workers with history of asbestos exposure [ 10 , 12 , 32 , 33 ]. The significant association between asbestos and COPD in a multi-exposure model (as we did not observe any collinearity between exposures, VIF < 3) can also be explained by the fact that asbestos may cause airflow limitation in the presence of other materials, vapors, gases, or dusts, as occurs in the real world of insulating material application [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found asbestos to be associated with COPD both in single and multi-exposure models. Our observations largely resonate with previous findings where progressive lung function decline and COPD have been reported in workers with history of asbestos exposure [ 10 , 12 , 32 , 33 ]. The significant association between asbestos and COPD in a multi-exposure model (as we did not observe any collinearity between exposures, VIF < 3) can also be explained by the fact that asbestos may cause airflow limitation in the presence of other materials, vapors, gases, or dusts, as occurs in the real world of insulating material application [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Evidence for the association of asbestos with other non-malignant respiratory conditions such as chronic obstructive pulmonary disease (COPD) and asthma is limited, and findings are inconsistent. While some studies showed a decline in lung function [ 10 ] and airway obstruction [ 11 , 12 ] associated with asbestos exposure, other reports do not confirm these associations and instead argue that this was a probable effect of smoking [ 13 , 14 , 15 ]. Moreover, despite a well-established relationship between asbestos and aggravated immunomodulation in the lungs [ 16 ], the association between asbestos exposure and the risk of pulmonary illnesses and concomitant infection has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to asbestos, dust and substances containing solvents such as paint, thinners and glues was also a causal factor for insomnia. Asbestos and solvents are hazardous chemicals that induce an inflammatory response in the respiratory system that may lead to pulmonary fibrosis, 27 ILD, 28 COPD, 29 and lung cancer. 30,31 Therefore, our results suggest that exposure to asbestos and solvents could lead to insomnia as a consequence of the development of severe respiratory diseases such as COPD, ILD and asthma .…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of the KL-6, SP-D, and MMP-2 concentrations and pulmonary function in patients with asbestosis, a higher serum KL-6 concentration was significantly negatively correlated with the FVC % predicted and DL CO % predicted, suggesting that high expression of KL-6 is associated with decreased pulmonary ventilation function and diffusion function in patients with asbestosis. The serum SP-D and MMP-2 concentrations were negatively correlated with DL CO % predicted, indicating impairment of pulmonary diffusion function [ 37 , 38 ]. The ROC curve analysis showed that the area under the curve of KL-6 was the largest, indicating that it is more effective than SP-D and MMP-2 in the diagnosis of asbestosis or silicosis.…”
Section: Discussionmentioning
confidence: 99%